PECULIARITIES OF POWDER-GAS FORMATION AT REFINING OF ALUMINIUM ALLOYS BY CHLORINECONTAINING COMPOUNDS - S. P. Zadrutskiy; G. A. Rumjantseva; B. M. Nemenenok; A. P. Bezhok (Литьë и металлургия)
The peculiarities of powder-gas formation at refining of aluminium alloys with chlorine-containing combinations are considered.